OUTCOMES OF PRIMARY POSTERIOR SAGITTAL ANORECTOPLASTY IN FEMALE PATIENTS WITH RECTO-VESTIBULAR FISTULA (Journal of Medical & Health Sciences Review, 2025)
BACKGROUND: Recto-vestibular fistula (RVF) is one of the most common forms of anorectal malformations (ARM) in female children. Primary posterior sagittal anorectoplasty (PSARP) is the preferred surgical technique; however, its outcomes may vary based on clinical and socioeconomic factors.To determine the postoperative outcomes of primary PSARP in female patients with recto-vestibular fistula presenting to a tertiary care hospital.METHODS: This descriptive study was conducted in the Department of Paediatric Surgery at Khyber Teaching Hospital, Peshawar. A total of 108 female patients with RVF who underwent primary PSARP were included. Demographic and socioeconomic data were recorded. Outcomes assessed included surgical site infection (SSI), recurrent fistula, and need for redo anoplasty. Associations between postoperative complications and patient factors (residence, maternal education, and age at surgery) were analyzed using Chi-square test, with p